Latihan Plyometric Hurdle Hopping untuk Meningkatkan Daya Ledak Otot Tungkai: Studi Kasus pada Atlet Bola Voli - Tasya Ghea Amanda; Adi Saputra Junaidi; Faridah Faridah (Prosiding Seminar Kesehatan Nasional, 2022)
This exercise was initiated by the author that the respondent, namely an athlete, would feel dissatisfied when jumping to smash while playing volleyball. The purpose of this explosive power exercise is to determine the effect of plyometric hurdle hopping on increasing the explosive power of the supporting muscles when jumping. There is also a measurement tool that is carried out before and after training, namely the vertical jump test. Explosive power is the ability of a person to exert maximum force. Explosive power is the ability to carry out activities suddenly and quickly by mobilizing all strength in a short time. Explosive power is one of the important biomotor components in sports activities, because explosive power will determine how high a person jumps, how hard a person can hit, how fast they run and so on. Sports that require explosive power, one of which is volleyball, is an activity that requires really good explosive power in its implementation